2014
DOI: 10.1038/sc.2014.233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms inducing autonomic dysreflexia during urinary bladder distention in rats with spinal cord injury

Abstract: Objectives: This study investigated the mechanisms inducing autonomic dysreflexia due to enhanced bladder-to-vascular reflexes in rats with spinal cord injury (SCI). Methods: SCI was produced by the transection of the Th4-5 spinal cord in female Sprague-Dawley rats. At 4 weeks after SCI, changes in blood pressure during graded increases in intravesical pressure (20-60 cm H 2 O) were measured in spinal-intact (SI) and SCI rats under urethane anesthesia. In five animals, effects of C-fiber desensitization induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…One of the major mechanisms inducing NDO after SCI is the morphological and functional plasticity of C-fiber bladder afferent pathways, which is evident as; (1) cell hypertrophy of lumbosacral bladder afferent neurons (Kruse et al, 1995; Yoshimura et al, 1998), (2) sprouting of CGRP- and substance P-positive C-fiber afferent central terminals in the spinal cord (Zinck et al, 2007; Zhang et al, 2008) and (3) increased expression of TRP channels such as TRPV1 and TRPA1 in lumbosacral bladder afferent neurons (Yoshizawa et al, 2014), as shown in previous studies using rats. Increased TRPV1 immunoreactivity in bladder suburothelial nerve fibers has also been detected in SCI patients with NDO (Brady et al, 2004; Apostolidis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major mechanisms inducing NDO after SCI is the morphological and functional plasticity of C-fiber bladder afferent pathways, which is evident as; (1) cell hypertrophy of lumbosacral bladder afferent neurons (Kruse et al, 1995; Yoshimura et al, 1998), (2) sprouting of CGRP- and substance P-positive C-fiber afferent central terminals in the spinal cord (Zinck et al, 2007; Zhang et al, 2008) and (3) increased expression of TRP channels such as TRPV1 and TRPA1 in lumbosacral bladder afferent neurons (Yoshizawa et al, 2014), as shown in previous studies using rats. Increased TRPV1 immunoreactivity in bladder suburothelial nerve fibers has also been detected in SCI patients with NDO (Brady et al, 2004; Apostolidis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Also, changes in neuropeptide expression, morphology and functioning of C-fiber afferents have been identified in both cats and rats post SCI. Various changes that have been observed include: (1) somal hypertrophy of bladder afferent neurons in L6-S1 dorsal root ganglia (DRG) (Yoshimura and de Groat, 1997; Yoshimura et al, 1998), (2) expansion of CGRP and substance P containing primary afferent fibers in the spinal cord (Zinck et al, 2007; Zhang et al, 2008), (3) increased expression of TRPV1 in bladder afferent neurons from L6-S1 DRG (Yoshizawa et al, 2014), and (4) increased excitability of bladder afferent neurons, which are capsaicin-sensitive, from L6-S1 DRG as revealed by patch clamp recordings (Yoshimura and de Groat, 1997; Takahashi et al, 2013). However, SCI-induced morphological and molecular alterations in bladder afferent neurons have yet to be well characterized in mice, although the mouse model has now become highly utilized due to its affinity to gene modification.…”
Section: Introductionmentioning
confidence: 99%
“…The micturition reflex in spinal intact condition is triggered by the small myelinated (Aδ) bladder afferent nerves responding to bladder distension and bladder contraction for voiding is evoked by stimulation of efferent nerves 1 . Voluntary control over micturition reflex is coordinated at the spinal cord level by the spinobulbospinal reflex pathway passing through the coordination centers (periaqueductal gray and pontine micturition center) located in the rostral brain stem.…”
Section: Introductionmentioning
confidence: 99%
“…These rats were anesthetized with urethane (0.9 g/kg subcutaneously) aided with isoflurane anesthesia. The dose of urethane was determined by our previous study (Yoshizawa et al, 2015) and preliminary experiments to suppress the body movement in spinal intact rats and spastic movements of the hind limbs in SCI rats during bladder distention. A 3Fr catheter (Hakko Co., Ltd., Nagano, Japan) filled with saline containing heparin was inserted into the common carotid artery to record the mean arterial pressure (MAP) and the mean heart rate (MHR).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study in SCI rats also revealed that AD induced by bladder distention is mediated by activation of resiniferatoxin-sensitive C-fiber afferents and is accompanied by increased expression of nerve growth factor (NGF) in the bladder wall and increased transient receptor potential (TRP) V1 channels in bladder afferent neurons (Yoshizawa et al, 2015). NGF overexpression in the bladder wall as well as in the spinal cord and dorsal root ganglia (DRG) after SCI is thought to be a major contributor to the induction of bladder afferent hyperexcitability and bladder overactivity (Seki et al, 2002; Yoshimura et al, 2006) as well as to AD during colon distention (Krenz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%